International Strategic Management - Anant R. Negandhi; A. Savara (Massachusetts: Lexington Books, 1989)
This volume about strategic management in the international arena focuses on economic efficiency and competitiveness. This volume has been divided into four parts: The first part contains articles providing a framework for examining international strategies. The second part considers decision making processes for an entire organization. The third part deals with international strategies at the functional level of an organization. The final part of the volume presents empirical research linking performance with different international strategies.
(NP(B/10803s
Keywords: competitiveness -- strategy -- foreign